Relationship between crude oil price and production levels—An empirical study of OPEC and non-OPEC states - Yang, Tzu-Yi; Chen, Ssu-Han; Yang, Yu-Tai; Chang, Hao-Hsin (Frontiers in Environmental Science, 2022)
To better understand the factors that affect crude oil price, this study uses monthly oil production by all OPEC and non-OPEC oil-producing states, as divided into the regions of Europe, the Americas and Asia according to the U.S. Energy Information Administration. The data also include West Texas Intermediate, Brent and Dubai oil prices from 1995 January to 2015 November. The Unbalanced Panel Random Effect Regression method was used to investigate the relationship between crude oil price and oil production and whether oil production by these countries significantly affected changes in crude oil price.